Back Matter Jurnal Litbang Industri Vol. 14 No. 1 Juni Tahun 2024 - Citra Setiawati (Institution for Industrial Research and Standardization of Industry - Padang, 2024)
Back Matter Jurnal Litbang Industri Vol. 14 No. 1 Juni Tahun 2024